Imaging of Cauda Equina Edema in Lumbar Canal Stenosis By Using Gadolinium-Enhanced MR Imaging: Experimental Constriction Injury - Kobayashi, S.; Uchida, K.; Takeno, K.; Baba, H.; Suzuki, Y.; Hayakawa, K.; Yoshizawa, H. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: It has been reported that disturbance of blood flow arising from circumferential compression of the cauda equina by surrounding tissue plays a major role in the appearance of neurogenic intermittent claudication (NIC) associated with lumbar spinal canal stenosis (LSCS). We created a model of LSCS to clarify the mechanism of enhancement within the cauda equina on gadolinium-enhanced MR images from patients with LSCS.METHODS: In 20 dogs, a lumbar laminectomy was performed by applying circumferential constriction to the cauda equina by using a silicon tube, to produce 30% stenosis of the circumferential diameter of the dural tube. After 1 and 3 weeks, gadolinium and Evans blue albumin were injected intravenously at the same time. The sections were used to investigate the status of the blood-nerve barrier function under a fluorescence microscope and we compared gadolinium-enhanced MR images with Evans blue albumin distribution in the nerve. The other sections were used for light and transmission electron microscopic study.RESULTS: In this model, histologic examination showed congestion and dilation in many of the intraradicular veins, as well as inflammatory cell infiltration. The intraradicular edema caused by venous congestion and Wallerian degeneration can also occur at sites that are not subject to mechanical compression. Enhanced MR imaging showed enhancement of the cauda equina at the stenosed region, demonstrating the presence of edema.CONCLUSION: Gadolinium-enhanced MR imaging may be a useful tool for the diagnosis of microcirculatory disorders of the cauda equina associated with LSCS.